Strötorvsanvändning i djurstallar : en litteraturgenomgång - Germundsson, Carin (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2006)
Peat litter has been used in animal houses for a long time. Because of its good ability to absorb liquid and nutrients from the manure it can create a dry surface for animals and a valuable manure product. Through changes in agricultural practises the use of peat litter has diminished and is to a great extent replaced by straw, sawdust and cutter shavings although Sweden is rich in peat-findings. The aim of this work was to summarize the presented knowledge about the used of peat litter, techniques, advantages and disadvantages and to compare with other commonly used litter materials. Articles on peat litter have been searched for in magazines, databases and books at SLU library. Visits to peat industries, interviews with peat producers and with peat researchers contributed to the material. Peat is not a uniformly material. The best peat litter is the undecomposed Sphagnum peat. This peat quality can absorb and hold liquid up to 12 times its own weight, 3-4 times more than straw. The ammonia binding capacity is 4 times better than that of straw, i.e. between 1.5 % and 3.5 % per dry matter of peat. Ammonia volatilization from animal husbandry is a great contributor to the total nitrogen deposition in nature. Deeplitter system with straw is, because of its active decomposition process, a greater emitter of nitrogen compared to peat and sawdust beds with slow decomposition rate. Peat manure leaks only small amounts of ammonia and it is not necessary to depose it before spreading and it is easy to spread. In animal houses using peat as litter the air is fresher and healthier for both animals and humans because of lower air concentration of ammonia. There are disadvantages with peat as litter. At moisture contents lower than 40 % there is a strong increase in the tendency to produce dust. It is therefore recommended to use peat with 40 to 50 % moisture content. The moisture pressure in peat beds is higher and it can be necessary to increase ventilation and to have supplemental heat during cold periods. The peat bed is sensitive to pressure; and the capacity to absorb and retain liquid, diminishes with increasing load. The significance of mycobacteria findings in peat and the potential production of mycotoxins in peat beds are unclear and needs further investigation. Peat is suitable as litter for dairy cows, young cattle and pigs. There is evidence for less foot problem and less labour input in peat litter systems. Horses benefit from peat beds by less suffering from cough and foot problem. In Finland it is common to use peat as litter in broiler breeding because of good effect on chicken health and growth. The peat manure is valuable and superior in nutrient content and as fertilizer. The ammonia losses from peat beds is low, the peat manure is easy to disperse and the nutrients is easy accessible for plants. Accordingly, peat litter possesses many qualities suitable for a good litter. The few negative sides can be compensated with technique. The unclearness about peat hygiene needs further studies. Peat sold for use in animal husbandry should be analysed for peat type, decomposition grade, moisture content and hygienic standard. Improved technical solutions are needed for handling and storing peat litter in the farm. Channels for peat trade and marketing are needed. To calculate and compare the cost of different litter systems from this literature review, is difficult. The studies are not easy comparable. Also prices vary with place, local connections and personal labour inputs. The impression is though that about equal quantity of dry matter of peat and straw litter is needed in similar kind of bedding systems and the price difference between purchased peat and straw is marginal. The advantage of peat litter systems is its higher manure content of 1-3 kg nitrogen, lower ammonia emission, less storing need and manure that is easier to disperse.